A Balancing Act at Times of Austerity: Matching the Supply and Demand for Skills in the Greek Labour Market - Konstantinos Pouliakas (Institute for the Study of Labor (IZA), 2014)
This paper provides an evidence-based assessment of the current situation prevailing in the Greek market for skills and jobs. The synthesis of available skills intelligence for Greece, the country most severely affected by the global economic crisis of 2008, is crucial as it is currently faced with tough decisions regarding the allocation of limited resources in the face of economic austerity. The paper engages in a comparative overview of Greece's performance on flagship Europe 2020 indicators on education and employment in relation to the EU. An empirical analysis of the incidence and determinants of skill mismatches in the Greek and EU job markets is also undertaken, using data from several European data sources. It is argued that a stronger vocational education and training pillar may constitute a valuable option for strengthening the links between the initial educational system and the labour market in Greece. But tackling skill mismatch requires skill development and skill utilization policies in the workplace. A stronger commitment to enhancing the skill content of jobs by employers via the adoption of high performance workplace practices, investment in continuous training, less reliance on casual labour and policies to support small and medium-sized enterprises in the war for talent are necessary if Greece is to make the most of its rich skills reserves.
Keywords: C25; I29; J11; J20; J24; J69; 330; skills; skill mismatch; Greece; vocational education and training; overeducation; shortages